Prostaglandins in glaucoma - Akram Rismanchian; Erfaneh Ghasami (مجله دانشکده پزشکی اصفهان, 2009)
The prostaglandin-related topical medications include latanoprost, unoprostone, travoprost, and bimatoprost. They are the new class of glaucoma medications. Prostaglandin analogs reduce intraocular pressure (IOP) by improving uveoscleral outflow primarily by altering the extracellular matrix. These prostaglandin-related agents or hypotensive lipids have a potent ocular antihypertensive agent when given once daily, with the exception of unoprostone, which is prescribed twice a day. Monotherapy with prostoglandins can reduce IOP levels by 29-32% over 1-12 months. Prostaglandins are quickly becoming important first-line agents in the treatment of glaucoma. They are well-tolerated and lack significant systemic side effects. They have the added benefit of once daily dosing. At high doses, these produce ocular inflammation and hypertension, but in smaller amounts, they reduce IOP. Prostaglandin analogs are contraindicated in any patient who is allergic or sensitive to these drugs, those with multiple risk factors, with iritis, herpes simplex keratitis or in the immediate postoperative period following intraocular surgery and patients with a history of uveitis and ocular herpes infection.